Invitation of non-attenders to colorectal cancer screening: impact on coverage by examination. (30th September 2020) - Majek, O; Ngo, O; Seifert, B; Suchanek, S; Zavoral, M; Jung, T; Dusek, L
Abstract: Issue: Colorectal cancer (CRC) has been among the most important cancer causes of death globally. CRC screening and early detection can decrease CRC incidence and mortality through timely removal of colorectal neoplasia or early CRC treatment. CRC screening has been initiated in the Czech Republic in 2000 for individuals over 50, with GPs having a key role in recruiting individuals to screening, offering faecal occult blood test (FOBT). Screening colonoscopy (CS) was added for individuals over 55 since 2009. Description of the problem: To increase uptake of CRC screening, personal invitation of non-attenders under 70 was implemented in 2014, along with temporary mass-media campaign. Health insurance companies have been sending invitations to those individuals without record of recent FOBT, CS or CRC treatment. The aim of our study was to evaluate impact of this policy on complete coverage by examination over 2013-2018. We defined the complete coverage by examination as the proportion of individuals aged 50-69 undergoing examination with CRC early detection potential (FOBT or CS for any indication) during past 3 years. We used newly established National Registry of Reimbursed Health Services as the source of data. Results: Complete coverage of the target population (2.7 million individuals aged 50-69) was 44.8 % in 2013. By 2016, the coverage increased to 54.6%. Therefore, almost 300, 000 individuals were newly covered by the relevant examinations. By 2018, the coverage decreased to 51.2%. When we consider only screening FOBT examinations, the coverage was 36.9 % in 2013, 45.2% in 2016, and 42.0% in 2018. Lessons: In the health system with accessible CS facilities, the policy of non-attenders' invitation for CRC screening resulted not only in increase in coverage by screening examinations; complete coverage also increased. Unfortunately, the positive effect has been fading out, and further actions to sustain high coverage are therefore warranted. Key messages: Invitation of non-attenders to colorectal cancer screening increased complete coverage of the target population by examination. Initial increase was followed by a slow decrease in coverage by examination, underlying the need for other actions to increase participation.